Postglacial emergence in the Canadian High Arctic: integrating glacioisostasy, eustasy, and late deglaciation - England, John (Canadian Journal of Earth Sciences, 1992)
Throughout the last glaciation, the Innuitian Sea, rather than glaciers, occupied many fiords and channels of the Queen Elizabeth Islands. Two alternative hypotheses, which constitute end members, are presented to account for the transgression of the Innuitian Sea between 18 and 8.8 ka, at which time it reached marine limit. Hypothesis A proposes that the last ice load was fully established by 18 ka and that it remained stable while sea level rose eustatically from approximately 60 m asl to marine limit by 8.8 ka. Hypothesis B proposes an advance of glaciers from present-day positions after 14 ka, when increased precipitation allowed rapid glacial loading to accompany the eustatic sea-level rise. By the early Holocene (when glaciers stood at the last ice limit) evidence suggests maximum warming and a shift to a negative mass balance.It is now recognized that the stable relative sea level at marine limit must record the balance between the rate of eustatic rise and the rate of uplift due to glacial unloading (thinning) between 8.8 and 7.8 ka. The rate of glacial unloading during this interval was low, approximately 1 m/100 years. Although the sea first penetrated inside the last ice limit by 8 ka, the first observed emergence was delayed until after 7.8 ka. By 7.6 ka many of the largest outlet glaciers from the Agassiz Ice Cap had retreated to positions equivalent to, or upvalley from, present-day margins. Nonetheless, between 7.8 and 7.2 ka, emergence progressed slowly (2 m/100 years), indicating that the large outlet glaciers retreated by calving, causing little change in the ice load. After 7.2 ka emergence was rapid, indicating that the regional glacial unloading was also rapid.It is proposed that the late deglaciation (Holocene) of the High Arctic favoured substantial postglacial emergence because the countering effect of the eustatic rise was largely completed by this time. Isobases drawn on the limit of the Innuitian Sea (the 8 ka shoreline) show a plunging ridge aligned with the south shore of Greely ...